Management of Emerging and Invasive Pests of Food Legumes and Cereals Germplasm in CWANA Region - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam; Darwish, Iman (The International Association for the Plant Protection Sciences, 2024)
The global economic cost of invasive pests has been estimated at $1.29 trillion over the past 50 years. Numerous reports of the invasion of transboundary pests into new areas have indicated that these pests are driven by agricultural intensification, international trade and climate change with adverse ecological, environmental and/or economic impacts. The Germplasm Health Units (GHUs) network that represents 11 CGIAR centers is a significant step to prevent the spread of invasive pests through global germplasm distribution activities. ICARDA’s GHU conducts regular monitoring, clearance and documentation of germplasm movement for food legumes and cereals in collaboration with the National Plant Protection Organizations (NPPOs) in Lebanon and Morocco, where ICARDA has platforms for crop breeding, germplasm multiplication, evaluation and genetic resources, by ensuring compliance with the International Plant Protection Convention (IPPC). It uses comprehensive methods that focus on preventing the entry, establishment and spread of invasive and emerging pests. In this context, ICARDA’s GHU applies international phytosanitary measures as part of inclusive and multidisciplinary procedures to eradicate and manage invasive and emerging pests to save germplasm. Testing of all exchanged germplasm is an essential task by investing in different modern diagnostic tools starting with a direct inspection method to DNA/RNA-based techniques. Rejected germplasm that cannot be treated or cured is terminated by autoclaving. In the last five years, ICARDA’s GHU tested about 506k seed samples with a total of 3,356k diagnostic reactions and removed 1.2% of the tested samples that were found to be infected with pests to facilitate exchanging of 1,580 consignments from/to 93 countries. By that ICARDA’s GHU demonstrates a proactive approach to addressing the challenges posed by invasive and emerging pests and serves as a key mechanism for ensuring the health and integrity of germplasm movement.